Factors affecting the attitudes and opinions of ICU physicians regarding end-of-life decisions for their patients and themselves: A survey study from Turkey - ARSLANTAŞ, MUSTAFA KEMAL (PUBLIC LIBRARY SCIENCE, 2020)
Introduction Turkey is constitutionally secular with a Muslim majority. There is no legal basis for limiting life-support at the end-of-life (EOL) in Turkey. We aimed to investigate the opinions and attitudes of intensive care unit (ICU) physicians regarding EOL decisions, for both their patients and themselves, and to evaluate if the physicians' demographic and professional variables predicted the attitudes of physicians toward EOL decisions. Methods An online survey was distributed to national critical care societies' members. Physicians' opinions were sought concerning legalization of EOL decisions for terminally ill patients or by patient-request regardless of prognosis. Participants physicians' views on who should make EOL decisions and when they should occur were determined. Participants were also asked if they would prefer cardiopulmonary resuscitation (CPR) and/or intubation/mechanical ventilation (MV) personally if they had terminal cancer. Results A total of 613 physicians responded. Religious beliefs had no effect on the physicians' acceptance of do-not-resuscitate (DNR) / do-not-intubate (DNI) orders for terminally ill patients, but atheism, was found to be an independent predictor of approval of DNR/DNI in cases of patient request (p< 0.05). While medical experience (>= 6 years in the ICU) was the independent predictor for the physicians' approval of DNI decisions on patient demand, the volume of terminal patients in ICUs (between 10-50% per year) where they worked was an independent predictor of physicians' approval of DNI for terminal patients. When asked to choose personal options in an EOL scenario (including full code, only DNR, only DNI, both DNR and DNI, and undecided), younger physicians (30-39 years) were more likely to prefer the only DNR option compared with physicians aged 40-49 years (p<0.05) for themselves and age 30-39 was an independent predictor of individual preference for only DNR at the hypothetical EOL. Physicians from an ICU with <10% terminally ill patients were less likely to prefer DNR or DNR and DNI options for themselves at EOL compared with physicians who worked in ICUs with a higher (> 50%) terminally ill patient ratio (p< 0.05). Conclusion Most ICU physicians did not want legalization of DNR and DNI orders, based solely on patient request. Even if EOL decision-making were legal in Turkey, this attitude may conflict with patient autonomy. The proportion of terminally ill patients in the ICU appears to affect physicians' attitudes to EOL decisions, both for their patients and by personal preference, an association which has not been previously reported.
Keywords: INTENSIVE-CARE-UNIT; DO-NOT-RESUSCITATE; SUSTAINING TREATMENT; WITHDRAWAL; SUPPORT; ILL; VARIABILITY; RELIGIOSITY; EUTHANASIA; AUTONOMY